CYBERBULLYING AND SPIRITUAL SOLUTIONS: QURANIC AND STOIC PERSPECTIVES IN DEALING WITH DIGITAL BULLYING - M. Hafiz Mauluddin Hazmi; Ahmad Permana; M. Akmal Maula; Ahmad Mujahid (Nida Al-Qur'an: Jurnal Pengkajian Islam, 2025)
In Indonesia, the issue of cyberbullying has become a serious concern, with UNICEF data showing that 45 percent of 2,777 young people aged 14 to 24 surveyed reported having experienced cyberbullying. This study provides practical solutions from the Qur'an to address the psychological impacts of cyberbullying, analyzed through a Stoic approach to facilitate understanding of the Qur'anic teachings. The research uses a library research approach with a qualitative descriptive method, aimed at providing an in-depth explanation of the subject matter. Primary data is obtained from tafsir books, while secondary data includes books, journals, and related articles. Data collection techniques employ the maudhu'i (thematic) method. The research findings suggest that the Qur'an provides solutions through prayers for protection to Allah, trust in Him (tawakal), and patience as responses to such behavior. Stoic philosophy views this Qur'anic solution as highly relevant due to its rational approach in dealing with cyberbullying. Furthermore, Stoicism emphasizes that through the application of these principles, individuals can not only overcome cyberbullying but also strengthen their character and become more resilient, wise, and better individuals overall.